Inferior gluteal artery surgical access for embolization of large internal iliac artery aneurysm in a hostile abdomen. Issue 4 (6th April 2019) - Tigkiropoulos, Konstantinos; Lazaridis, Ioannis; Stavridis, Kyriakos; Tympanidou, Marianthi; Karamanos, Dimitrios; Saratzis, Nikolaos
Abstract: Introduction: Internal iliac artery aneurysms (IIAA) are a rare entity compared with all aortoiliac aneurysms. Continuous expansion due to retrograde flow from runoff vessels can lead to rupture with devastating results. Exclusion of the aneurysm represents a challenging procedure especially if the access is limited and the patient has a history of reoperations in the pelvic region. Case: A 78-year-old man with a history of endovascular aortic repair, coverage of internal iliac arteries and right hemicolectomy for adenocarcinoma of ascending colon presented with a rapidly expanding right IIAA (8.8 cm) due to type II endoleak. He successfully treated with coil embolization through inferior gluteal artery surgical access. Conclusion: Inferior gluteal artery surgical access for embolization of internal iliac aneurysms in patients with hostile abdomen or in cases where antegrade route has already been excluded, is a feasible technique.